POPULARISATION PRACTICE OF DOCUMENTARY HERITAGE AT THE STATE AGENCY “АРХИВИ” GABROVO DEPARTMENT - Burceva, Rita; Koycheva, Tsvetomira; Gecheva, Katia (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2016)
The objective of the research is to describe the popularisation experience of documentary heritage at the department of the particular archive in Bulgaria, emphasizing the specific aspects of this practice in order to formulate recommendations for similar activities in Latvia. The methods used in the research: analysis of some individual aspects of popularisation of the documentary heritage based on the normative enactments governing the activity of archives in Bulgaria, case analysis. Popularisation of documents is the body of communication events, which are used to cover a wide circle of persons and institutions. It is directly connected to the social, political, cultural life in the country and region and it is aimed at the reflection of upbringing, educating, cultural, and science matters. Each department of the archive plans and implements the popularisation events of the documentary heritage separately from one another or in cooperation with museums, creative associations, scientific institutions and education establishments, other governmental and public institutions, the mass media, etc. They are initiated in order to introduce or remind the public of any significant events, processes, persons. There are varied forms of exhibition offerings: mobile and stationary, permanent and temporary, taking place in the premises of the archive and in the specifically adopted environment outside of it (in other institutions or outdoors), including in the electronic form. The archive of Gabrovo has substantial experience of work with the student group excursions from the city and the nearby neighbourhood, which require special preparation and ability to communicate with the youth, using understandable and acceptable to them materials and visual aids. Main conclusions: Despite being dully planned, in most cases under the situation of limited resources the popularisation events of the documentary heritage are based on the personal initiative, experience in building contacts and the ability to find some possibilities for improvement of this work through purposeful customer-oriented communication of the employees of the Archive of Gabrovo. It is important to use the personal connections and unforeseen events creatively in the work with the current and potential creators. In the public space the Archive Department of Gabrovo positions itself as an open institution that is ready to cooperate with all organisations and individuals interested for comprehensive and quality satisfaction of all public needs at all levels.